Relationship of the different Ca sites in the matrix with luminescence properties of orange‒red emitting Li0.04Ca0.96-xSiO3:Smx phosphors. Issue 10 (15th May 2022) - Liang, Chunping; Huang, Xuefei; Huang, Weigang
Abstract: Li0.04 Ca0.96-x SiO3 :Smx orange‒red emitting phosphors were synthesized using the sol-gel method. X-ray diffraction, Rietveld refinement of XRD patterns, Fourier transform infrared spectroscopy and ﬂuorescence spectrophotometry were used to characterize the crystal structure, sites of cationic Ca and luminescence properties of the prepared phosphors. The relationship of the different Ca sites in the matrix with the luminescence properties was analysed. The results indicate that the prepared phosphors reveal a β-CaSiO3 phase with a monoclinic crystal structure and space Group P21/a. As the Sm 3+ concentration increases, the unit cell volume of phosphors and the Ca–O band lengths of different Ca sites decrease due to substitution of Ca 2+ by smaller Sm 3+ ions. By excitation at 404 nm, Li0.04 Ca0.96-x SiO3 :Smx phosphors exhibit warm orange‒red light, corresponding to the electron transitions from 4 G5/2  →  6 H5/2 (567 nm), 4 G5/2  →  6 H7/2 (605 nm) and 4 G5/2  →  6 H9/2 (651 nm) of Sm 3+ . The concentration quenching phenomenon appears at Sm 3+ concentrations beyond 0.02. The refinement results demonstrate that three cationic Ca sites, named Ca1, Ca2 and Ca3, exist in the β-CaSiO3 host lattice. The Ca 2+ ions at Ca1 and Ca2 sites are coordinated with six oxygen ions, leading to the same coordination number (CN). The Ca 2+ ion located at Ca3 site has seven coordination numbers. The Ca1 site possesses a smaller lattice distortion and better symmetry than those of Ca2 and Ca3 sites. However, the Ca3 site exhibits the largest lattice distortion and poor symmetry. The Sm 3+ present in symmetric Ca1 sites in the matrix illustrates the strong emission intensity, long luminescence lifetimes and good thermal stability.